Genetic analysis of bioactive compounds and antioxidant properties in lettuce (Lactuca sativa) - SAHA, SWATI; KALIA, PRITAM; SUREJA, A K; SRIVASTAVA, ARPITA; SARKAR, S K (The Indian Journal of Agricultural Sciences, 2016)
Leaves of lettuce (Lactuca sativa L.) are the store house of various phytonutrients which have protective properties. Being an important dietary leafy vegetable, it is primarily consumed fresh as salad and in sandwiches, burgers etc. Its beneficial effects are primarily due to the presence of different phytochemicals such as ascorbic acid, carotenoids, polyphenols and fibre which helps in protecting key biological constituents such as lipoproteins, membranes and DNA. However, systematic biochemical nutrient analysis has not been carried out in this important salad vegetable so far. In the present investigation, 36 genotypes were analysed for phytochemicals such as total carotenoids, lycopene, ascorbic acid, total phenolic content, Cupric ion Reducing Antioxidant Capacity (CUPRAC) and Ferric Reducing Antioxidant Power (FRAP). The CUPRAC ranged from 0.05 to 1.98 Î¼mol trolox/g with the highest content in Stem lettuce Angustana, whereas FRAP ranged from 0.06 to 4.70 Î¼mol trolox/g showing, thereby, a considerable variation amongst genotypes. Total phenolics ranged from 41.94 to 501.88 Î¼g gallic acid/g fresh weight. Total carotenoids were found in appreciable amount in Wo Suen (46.13 mg/100g fresh weight), whereas lycopene in New Chicken (17.01 mg/100g fresh weight). Ascorbic content ranged from 1.14 to 3.75 mg/100g fresh weight, whereas per cent moisture ranged from 86.50 (NVRS 10:001818) to 97.32 (Sheetal). Positive correlation was observed between total carotenoids and lycopene, chlorophyll b with chlorophyll a, total chlorophyll with both chlorophyll a and b, FRAP with CUPRAC and phenols with total chlorophyll, chlorophyll a and b. Maximum phenotypic and genotypic coefficients of variance were calculated for FRAP (165.98, 165.98) followed by CUPRAC (122.10,122.10) and lycopene content (83.33, 80.84), respectively. These genotypes can be further utilized for development of multinutrient rich varieties. Regular consumption of lettuce can go a long way in tackling osteoporosis, anemia, and cardiovascular related problems.